Health status, heat preparation strategies and medical events among elite cyclists who competed in the heat at the 2016 UCI Road World Cycling Championships in Qatar. Issue 16 (28th January 2020) - Racinais, Sebastien; Nichols, David; Travers, Gavin; Moussay, Sebastien; Belfekih, Taoufik; Farooq, Abdulaziz; Schumacher, Yorck Olaf; Périard, Julien D
Abstract : Purpose: Assess the health status and heat preparation strategies of athletes competing in a World Cycling Championships held in hot ambient conditions (37°C, 25% relative humidity, wet-bulb-globe-temperature 27°C) and monitor the medical events arising during competition. Methods: 69 cyclists (~9% of the world championships participants) completed a pre-competition questionnaire. Illnesses and injuries encountered by the Athlete Medical Centre (AMC) were extracted from the race reports. Results: 22% of respondents reported illness symptoms in the 10 days preceding the Championships. 57% of respondents had previously experienced heat-related symptoms (cramping most commonly) while 17% had previously been diagnosed with exertional heat illness. 61% of the respondents had undergone some form of heat exposure prior to the Championships, with 38% acclimating for 5 to 30 days. In addition, several respondents declared to live in warm countries and all arrived in Qatar ~5 days prior to their event. 96% of the respondents used a pre-cooling strategy for the time trials and 74% did so before the road race (p<0.001), with ice vests being the most common. The AMC assessed 46 injuries and 26 illnesses in total, with three cyclists diagnosed with heat exhaustion. Conclusions: The prevalence of previous heat illness in elite cyclists calls for team and event organisation doctors to be trained on heat illness management, including early diagnosis and rapid on-site cooling. Some cyclists had been exposed to the heat prior to the Championships, but few had a dedicated plan, calling for additional education on the importance of heat acclimation. Pre-cooling was widely adopted.